A New Measurement Technique of the Characteristics of Nutrient Artery Canals in Tibias Using Materialise's Interactive Medical Image Control System Software. (15th December 2015) - Li, Jiantao; Zhang, Hao; Yin, Peng; Su, Xiuyun; Zhao, Zhe; Zhou, Jianfeng; Li, Chen; Li, Zhirui; Zhang, Lihai; Tang, Peifu
Abstract : We established a novel measurement technique to evaluate the anatomic information of nutrient artery canals using Mimics (Materialise's Interactive Medical Image Control System) software, which will provide full knowledge of nutrient artery canals to assist in the diagnosis of longitudinal fractures of tibia and choosing an optimal therapy. Here we collected Digital Imaging and Communications in Medicine (DICOM) format of 199 patients hospitalized in our hospital. All three-dimensional models of tibia in Mimics were reconstructed. In 3-matic software, we marked five points in tibia which located at intercondylar eminence, tibia tuberosity, outer ostium, inner ostium, and bottom of medial malleolus. We then recorded Z -coordinates values of the five points and performed statistical analysis. Our results indicate that foramen was found to be absent in 9 (2.3%) tibias, and 379 (95.2%) tibias had single nutrient foramen. The double foramina was observed in 10 (2.5%) tibias. The mean of tibia length was 358 ± 22 mm. The mean foraminal index was 31.8% ± 3%. The mean distance between tibial tuberosity and foramen (TFD) is 66 ± 12 mm. Foraminal index has significant positive correlation with TFD (r = 0.721, P < 0.01). Length of nutrient artery canals has significant negative correlation with TFD (r = −0.340, P < 0.01) and has significant negative correlation with foraminal index (r = - 0.541, P < 0.01 ).